PENGARUH INTELLECTUAL CAPITAL TERHADAP ASSET QUALITY PADA INDUSTRI PERBANKAN DI INDONESIA - Rizqa Ayu Nurmalita; Ahmad Muslim; Maria C. Widiastuti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to analyze the effect of the causal relationship between intellectual capital on asset quality at banks in Indonesia. This study uses secondary data derived from the Bank's annual financial statements that have been audited and listed on the Indonesia Stock Exchange (IDX) throughout 2015 to 2020. By applying the purposive sampling method in order to obtain 38 banks as samples. Processing and analyzing data in conducting hypothesis testing using multiple regression analysis which is then processed with the Eviews 9 program. The use of Asset Quality as an indicator of the banking risk profile uses a Non-Performing Loan (NPL) measurement approach. Meanwhile (VAICTM), along with its components, namely human capital efficiency (HCE), structural capital efficiency (SCE) and capital employed efficiency (CEE) are used as approaches in measuring intellectual capital. The control variables used are bank age (BAGE) and bank size (BSIZE). The results of the study indicate that intellectual capital generally affects the asset quality of banks in Indonesia significantly positively. When intellectual capital is divided into its components, this study proves that there is a significant relationship to asset quality. Negatively with human capital efficiency (HCE) while positively with structural capital efficiency (SCE). While the control variable Bank age (BAGE) was proven to have a significant negative effect on asset quality. The results of this study prove that the Bank's management can optimize intellectual capital along with structural capital and human capital to maintain and maintain asset quality. Furthermore, the results of this study are expected to have direct implications for the development of banks in the era of knowledge-based economy. This study analyzes the relationship between intellectual capital and its relationship to bank asset quality, which is still minimally studied empirically in banking in Indonesia.